Antibiotic Dosing in Patients With Acute Kidney Injury: "Enough But Not Too Much". (March 2016) - Lewis, Susan J.; Mueller, Bruce A.
Increasing evidence suggests that antibiotic dosing in critically ill patients with acute kidney injury (AKI) often does not achieve pharmacodynamic goals, and the continued high mortality rate due to infectious causes appears to confirm these findings. Although there are compelling reasons why clinicians should use more aggressive antibiotic dosing, particularly in patients receiving aggressive renal replacement therapies, concerns for toxicity associated with higher doses are real. The presence of multisystem organ failure and polypharmacy predispose these patients to drug toxicity. This article examines the pharmacokinetic and pharmacodynamic consequences of critical illness, AKI, and renal replacement therapy and describes potential solutions to help clinicians give "enough but not too much" in these very complicated patients.